Parental Perspectives on a Behavioral Health Music Intervention for Adolescent/Young Adult Resilience during Cancer Treatment: Report from the Children’s Oncology Group - Docherty, Sharron L. (2012)
PURPOSE: This paper describes parental perspectives on the helpfulness and meaningfulness of a behavioral health music therapy intervention targeted to adolescents/young adults (AYA) with cancer undergoing stem cell transplantation. We demonstrate how qualitative methods may be used to understand critical aspects of an intervention and mechanisms by which the intervention impacts the target AYA outcomes resilience and quality of life. METHODS: A qualitative descriptive design was used to obtain parents’ perspectives. Maximum variation purposive sampling was used to sample 16 parents whose AYA had been randomized to the intervention group. A semi-structured, open-ended interview was conducted between 100 and 160 days following their AYA’s transplant. RESULTS: Results are grouped into three categories: (1) helpfulness and meaningfulness of the intervention to AYA adjustment to the transplantation experience; (2) helpfulness and meaningfulness of the intervention for parents; and (3) AYA ability to participate in the intervention during acute phase of transplantation. CONCLUSIONS: Parents observed and interacted with their AYA who participated in a targeted, behavioral intervention. Thus parents were able to describe mechanisms through which the intervention was helpful and meaningful for the AYA and indirect personal benefits for themselves. The results suggest the importance of the targeted outcomes identified in the Resilience in Illness Model and mechanisms of action in the Contextual Support Model of Music Therapy and identifies approaches for future study.